The Beginning of Speech / The Speech of the Beginning - Duque, Félix (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
In the beginning was the Word… already and since forever uttered. «Was», and not «hasbeen», as if it was a punctual fact, buried in the past, instead of being the cordial renewal of a latency:nostalgia of arché. This study attempts —not without a certain fear— to deal with the very commencement of John’s Prologue (the beginning of speech), going deep into arduous passages of the Epistle to thePhilippians (unbearable for a pagan or metaphysic religiosity), and sounding out —as far as possible—Schelling’s depths: all of this, around a vortex as incomprehensible (i. e.: unvordenklich, beforehandunthinkable) as irresistibly fascinating: the perichóresis of Deus-Trinitas. And in its deepest womb, the paradox into which every thought sinks: it is only possible to be one self if since forever, essentially, one is another; if one is constantly and lovely turned to (prós) the other.
Keywords: speech (Rede; not Sprache); beginnning (arché); emptiness; potency; sameness/otherness